Effect of neurotoxins from the scorpion venom Lychas mucronatus Fabricius, 1708 on the exitatory nerve - Anh, Hoang Ngoc; Maximov, G. V.; Berezin, B. B.; Yamsskov, I. A. (Academia Journal of Biology, 2015)
These neurotoxins decrease the action potential (AP) value depending of the neurotoxin molecular weights (Mw). The AP rate is independent of the neurotoxin Mw indicating the direct influence of the toxins on Na+ and K+ channels located on the Ranhe oversize and no influence on the myelin nerve fibre state. No dependence is observed between the neurotoxin Mw and the threshold excitation of the nerve fibres. Thus the amplitude of the action AP of the new neurotoxins from the scorpion venom Lychas mucronatus is dependent on the Mw, while the rate and the threshold of its nerve excitatation is not.